2007
DOI: 10.1002/clc.20034
|View full text |Cite
|
Sign up to set email alerts
|

Left bundle‐branch block—pathophysiology, prognosis, and clinical management

Abstract: Summary: Given its broad use as a screening tool, the electrocardiogram (ECG) has largely become one of the most common diagnostic tests performed in routine clinical practice. As a result, the finding of left bundle-branch block (LBBB) in the absence of a well-defined clinical setting has become relatively frequent and raises questions and often concerns. While in the absence of clinically detectable heart disease LBBB does not necessarily imply poor outcomes, physicians should be aware of the role of LBBB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 58 publications
0
57
0
1
Order By: Relevance
“…8 Although definitive explanations are lacking, it has been hypothesized that this effect could be a consequence of subsequent impaired left ventricle contractility, dyssynchrony, worsened mitral regurgitation, and higher risk of progression to complete atrioventricular (AV) block and sudden death. 9 Whether this specific conduction disturbance could have an ominous impact in patients undergoing TAVI is still unclear, because limited data have specifically focused on this topic so far. We thus sought to evaluate, in a multicenter registry of patients treated in high-volume centers, the prognostic significance of persistent LBBB after TAVI with the CoreValve Revalving System (CRS).…”
mentioning
confidence: 99%
“…8 Although definitive explanations are lacking, it has been hypothesized that this effect could be a consequence of subsequent impaired left ventricle contractility, dyssynchrony, worsened mitral regurgitation, and higher risk of progression to complete atrioventricular (AV) block and sudden death. 9 Whether this specific conduction disturbance could have an ominous impact in patients undergoing TAVI is still unclear, because limited data have specifically focused on this topic so far. We thus sought to evaluate, in a multicenter registry of patients treated in high-volume centers, the prognostic significance of persistent LBBB after TAVI with the CoreValve Revalving System (CRS).…”
mentioning
confidence: 99%
“…Clinical and echocardiographic follow-up of LBBB is mainly related to dilated cardiomyopathy and heart failure. However, there are some epidemiological studies that provide evidence of a worse outcome in a population affected with LBBB [2]. Perhaps in this case biventricular depolarization will prevent mechanical dyssynchrony and in the future an evolution to a dilated cardiomyopathy by ventricular remodeling [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…CLBBB may precede the onset of heart disease for years, leading some investigators to consider it a possible precursor to latent cardiomyopathy [2]. Although some studies have suggested that CLBBB may have a benign prognosis [7,8], most have indicated that CLBBB has poorer prognosis in comparison to normal intraventricular conduction and also compared to right bundle branch block, with a median survival of 5 years from the time of diagnosis [2,4,5,7,[9][10][11][12]. Furthermore, the electrocardiography (ECG) characteristics of CLBBB obscure the application of common criteria for the diagnosis of left ventricular hypertrophy (LVH), myocardial infarction (MI) in the chronic phase, and diseases that cause modifications on the ST-T segment, establishing a need for other studies to assess these heart diseases in the presence of CLBBB [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%